Public Administration at A Crossroad: Policy on Agricultural Extension within Digital Society - Wahyu Riawanti; Kurnia Cahyaningrum Eﬀendi (Policy & Governance Review, 2017)
The study is aimed to reveal the public administration process in a challenging digital society. Facing the globalization, agriculture sector in Indonesia cope with the same challenge. In term of modernization, the role of agricultural extension is considered as one of the main factors in transferring technology and knowledge to the farmers. The case study was taken on Indonesian agriculture policy in Yogyakarta Province to reveal two diﬀerent aspects namely (a) the dynamic and relevance of agriculture policy to deal with nowadays digital society challenge and (b) how the extension agents respond the policy in terms of digitalized society and globalization. The qualitative data was taken from in-depth interview and FGD with extension agents in Yogyakarta province were used for the research main data. The research result has shown that the impact varied from diﬀerent extension groups/districts. The characters of extension agents and mostly Indonesian agriculture sectors are mostly the aging agriculture labors and lower technology application. This study results on how the agriculture policy was historically put the entity of extension agents as merely “object of development”. This phenomena fnally has to cope with recently global agriculture problem. The study